Primary Candida guilliermondii Infection of the Knee in a Patient without Predisposing Factors - Gun Woo Lee; Tae-Hun Kim; Jung-Hwan Son (Case Reports in Medicine)
Isolated primary candidal infection of joint is extremely rare, with only a few reported cases. It occurs as a result of accidental implantations of fungus during traumatic procedures, such as surgery, and is usually reported in patients with predisposing factors such as immunosuppression, malignancy, and drug abuse. If left untreated, irreversible deformity and pain with severe osteoarticular destruction occur. Thus, early diagnosis and treatment are important. This paper presents a case of 72-year-old man with primary C. guilliermondii infection of knee joint without predisposing factors and previous traumatic procedures, who was misdiagnosed with advanced degenerative osteoarthritis. Our case is the second case of primary C. guilliermondii arthritis of knee to be reported in the English-language literature and the first to be successfully treated with total knee arthroplasty following IV amphotericin B and oral fluconazole. Primary candidal infection of joint is generally asymptomatic or involves only mild pain and swelling in the affected knee. Thus, although the majority of knee joint infections are of a pyogenic or tuberculous origin, if a patient complains of mild pain and swelling in the knee and has mild signs of infection, the possibility of fungal infection should be considered.